(untitled) (L’architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2016)
In 2014, the Aseer Governorate Municipality in collaboration with the General Authority of Tourism and Antiquities announces a competition for urban and architectural design for a new foundation tourist city in an area just to the north-east of Abha. The one that is going to be described is the winning project, designed by the architects Francesco Cellini (group leader), Luigi Franciosini and Giovanni Longobardi, professors at the Department of Architecture of the Roma Tre University. The â€œAbha Dreamâ€ is the dream of a new city, for leisure, tourism and commerce, functional and with a rich offering of services, water and vegetation. It is a utopia that reflects the current desires of Abha (retracing its perimeter and defining an area of 11 square kilometres); its form embodies a city that develops primarily along a lush wadi, resembling and recalling the image of paradise in Islamic culture: a place of rich shadows and fountains of water.